The Effects of Capital Structure and Good Corporate Governance on Company Value - Minda Utami, Eristy; Nuryani, Fani; Novan Setiawan Nugraha, Deden (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to analyze the effect of capital structure and good corporate governance on firm value in the plantation subsector listed on the IDX for the period 2012-2016. Capital structure is measured by debt-to-equity ratio, good corporate governance is measured by independent commissioners and institutional ownership, and company value is measured by Tobin’s Q. The research method used is a descriptive statistical method. The tests performed consist of classical assumption tests, panel data tests, F tests, and t tests. The population in this study is the plantation sub-sector companies listed on the Stock Exchange in the period of 2012-2016, as many as 16 companies. The selection of samples used is the purposive sampling method, with the number of sample companies, namely as many as 9 companies. The data analysis used is panel data regression analysis with multiple linear regression methods at a significance level of 5%. The results showed that capital structure as measured by debt-to-equity ratio had a positive effect on firm value, good corporate governance (GCG) as measured by independent commissioners had no effect on company value, and good corporate governance as measured by institutional ownership had a positive effect on firm value.